Amma, I know you: a study on mother-daughter affiliation among indians - Menakah Thiagaras (2017)
The emotional bond between a mother and her progeny can be considered as one of the most crucial and primary forms of social relationships, especially among humans. As a result, countless studies have been conducted to examine the neural circuits involved when catering to this bond in terms of facial processing. However, there is a lack of neurophysiological research done on maternal attachment between adult children and their mothers. In this present study, we aim to extend the literature on maternal attachment through investigating the neural circuits involved in maternal facial recognition. We measured adult daughter’s prefrontal activation through functional near-infrared spectroscopy while they were viewing facial stimuli of their own mothers and female strangers. Since past research have suggested that regions in the prefrontal cortex play a significant role in facial processing, the present study will focus only on the prefrontal hemodynamic responses. Surprisingly, results showed that while viewing female strangers’ faces, brain regions in the dorsomedial prefrontal cortex showed more activation than compared to mothers’ faces. Furthermore, our study also revealed that there were no differences in activation while looking at the past and recent faces of mothers. Also, when comparing between parenting styles, significant differences were found in the neural responses to facial stimuli of the mothers. These results concur the importance of the role of the mother and also display a trend in neural responses that remarkably are the opposite of previous literature on maternal face recognition.